Development of the annual incidence rate of fracture in children 1980–2018: a population-based study of 32,375 fractures - Larsen, Andreas V; Mundbjerg, Esben; Lauritsen, Jens M; Faergemann, Christian (Acta Orthopaedica, 2020)
Background and purpose — Pediatric fractures are a common cause of morbidity. So far, no larger Danish study has described the development in the incidence rates. Therefore, we describe the development in the incidence rates of pediatric fractures in the time period 1980–2018 and the frequency of the most common type of fractures. Patients and methods — This is a retrospective register study of all children aged 0–15 years with a fracture treated in the Emergency Department at Odense University Hospital, Denmark, between 1980 and 2018. For all cases, information on age, sex, date of treatment, diagnosis, and treatment was obtained from the patient registration system. Based on official public population counts we estimated age and sex-specific annual incidence rates. Results — 32,375 fractures were included. In the study period the incidence rate decreased by 12%. The incidence increased until the early 1990s. Thereafter incidence rates decreased until 2004–09, from then onward increasing towards the end of the study period. The highest age-specific incidence rate in boys of 522 per 10,000 person-years was at 13 years of age. In girls the age of the highest incidence rate decreased from 11 years in 1980 to 10 years in 2018. Fracture of the lower end of the forearm, the clavicle, and the lower end of the humerus had the highest single fracture incidence rates. Interpretation — The incidence rate of pediatric fractures decreased in the study period by 12%. The highest single fracture incidence rates were for fracture of the lower end of the forearm, the clavicle, and the lower end of the humerus. As the first longitudinal Danish study of pediatric fractures this study is a baseline for evaluating future interventions and future studies.